EZgate - A ﬂexible Gateway for the Internet of Things - Teubler, Torsten; Walther, Ulrich; Hellbrück, Horst (Electronic Communications of the EASST, 2011)
Two years ago a survey of the wireless world research forum predictedthat in the year 2017 there will be seven trillion wireless devices for seven billionhumans which is equivalent to 1000 devices per human being on the average. Thefuture will show if this incredible number will be reached but for sure we will seean increasing number of wireless devices forming the Internet of the future. Thenew evolving “Internet of Things” is one of the challenging research topics today.With many wireless resource constraints devices, smart gateways integrating thesesmall battery-powered devices into the future Internet will play a major role for thesuccess of the Internet of Things. These gateways will work as a communicationendpoint or proxy enabling transparent services including mechanisms for seman-tic service discovery, Quality of Service (QoS), and performance enhancing prox-ies (PEPs). In this work we will introduce a fully operable TCP/IP-Stack EZgatewritten in Java that allows designing and implementing such gateways for wirelessnetworks in a ﬂexible and fast approach and compare it with related work. We willdemonstrate how the protocols in this stack can be assembled in a ﬂexible manner,creating various types of gateways and can be easily extended to implement crosslayer techniques. Finally, we evaluate the performance of the implementation fordelay and throughput performance to show that EZgate is suitable for use in a pro-ductive environment.